Electrokinetic Remediation of Zinc and Copper Contaminated Soil: A Simulation-based Study - Rezaee, Milad; Kargar Ghomesheh, Pourya; Mohammad Hosseini, Arash (Civil Engineering Journal, 2017)
Electrokinetic is an effective and innovative method to remediate different kinds of soils, especially low permeable fined-grain soils such as silty and clayey soils. In this method, by applying a direct-current electric field into a contaminated soil resulted in different transport phenomena, the soil is remediated. This paperâs objective is to propose a numerical model for Electrokinetic remediation of zinc and copper contaminated soils. Different transport phenomena including ion migration, electroosmosis flow, and diffusion were taken into account in the model. Chemical reactions such as precipitation/dissolution, adsorption onto the soil surface, and water chemical equilibrium were considered as well. Furthermore, instead of simplified boundary conditions (Neumann or Dirichlet) that cannot properly reflect the reality of the Electrokinetic remediation process, the realistic boundary conditions were used with consideration of flux and electrolysis reaction at the electrodes. The simulation results compared with the available experimental data in the literature. The coefficient of determination and the index of agreement indicated that the present model is consistent with the testsâ results. Thus, the assumptions considered in the present study are acceptable.